Accounting for the rise in unfunded public pension liabilities: faulty counterfactuals and the allure of simple gain/loss summations*. (3rd October 2016) - COSTRELL, ROBERT M.
Abstract: This paper provides a methodological critique of an influential method for assessing the impact on the Unfunded Accrued Liabilities (UAL) of the gap between assumed and actual investment returns over extended periods, and offers a sound replacement. The method in question simply sums over time the components of the annual actuarial gain/loss report. This implicitly assumes that in the counterfactual exercise, the interest on the additional UAL is covered dollar-for-dollar by amortization. But under actual funding formulas amortization usually varies less than interest. This means there are large intertemporal interactions between the gap in investment returns and subsequent shortfalls between contributions and interest. Using the actual funding formula in the counterfactual can lead to much higher estimates of the UAL impact of the gap in investment returns because it does not assume away these interactions. This method can more accurately inform policy-makers, regarding the importance of cutting the assumed rate of return.